PENGARUH REPUTASI KANTOR AKUNTAN PUBLIK (KAP), AUDIT TENURE, DAN BIAYA AUDIT TERHADAP KUALITAS AUDIT (Studi Empiris Perusahaan Jasa Sektor Keuangan yang Terdaftar di BEI Tahun 2014 - 2016) - Ilham Naffis Ramadhan; Herry Laksito (Diponegoro Journal of Accounting, 2018)
This research is contucted in order to obtain empirical evidence and analyze the influence of Public Accountant Firm (KAP) reputation, audit tenure and audit cost towaard audit quality at manufacturing company listed in Indonesia Stock  Exchange (IDX). In this research, the dependent variable that used is audit quality and the independent variables that exiist are the reputation of KAP, audit tenure, and Fee audit. The result of hypothesis test shows that reputation of public accountant office (KAP) take effect toward audit quality. Nevertheless, audi tenure and audit fees are not proven affecting audit quality